Role of Fusarium graminearum STE3 Receptor in Mediating Fungal Hyphal Chemotropism and Pathogenesis - Sharma, Tanya (Université d'Ottawa / University of Ottawa, 2023)
Fusarium head blight is one of the devastating diseases of cereal crops caused by Fusarium graminearum. This fungal pathogen produces mycotoxins like deoxynivalenol (DON), depositing it in wheat kernels and making them unfit for consumption. In addition, it causes decreases in the nutritional content of the wheat. Since wheat contaminated with DON above permissible levels must be discarded, it also leads to huge economic losses to the farmers. Fungi have a complex network of hyphae that lets them sense their surroundings. These are advantageous for nutrition and pathogenesis needs. Fungi have evolved nuanced mechanisms to orient hyphae towards external cues. Through our studies described in Chapter 2, we have elucidated the role of Ste3 GPCR in mediating fungal chemotropism towards peroxidases (previouly shown for Ste2). Both of these receptors were shown to activate the CWI-MAPK pathway in response to peroxidases. In addition, pathology assays on germinating wheat coleoptiles and detached Arabidopsis leaves showed that a Ste3 knockout strain was significantly compromised in its' ability to cause lesion development. In Chapter 3, we investigated the heterodimerization between FgSte3 and FgSte2 in response to peroxidase and a potential HRP-derived ligand of fungal origin. BRET and pull-down experiments confirmed the interaction. Chapter 4 consists of ongoing projects that go beyond the scope of the timeline for this dissertation. This includes establishing an Sf21 insect cell expression platform for the expression and purification of full length FgSte3 with a goal to elucidate the structure of the protein. Together these studies enhance our understanding of the mechanistic aspects of fungal pathogenesis and represent a step forward toward the development of novel anti-fungal compounds.
Keywords: Fungal pathogens; GPCR research